SG-PBFT: A secure and highly efficient distributed blockchain PBFT consensus algorithm for intelligent Internet of vehicles - Xu, Guangquan; Bai, Hongpeng; Xing, Jun; Luo, Tao; Xiong, Neal N.; Cheng, Xiaochun; Liu, Shaoying; Zheng, Xi (Journal of parallel and distributed computing, 2022)
•Our algorithm is more efficient, has less communication overhead, and has greater throughput than the original PBFT algorithm.•We propose a Vehicle - Service Provider - Roadside Unit architecture to ensure the orderliness and safety of vehicles.•We propose an identity authentication scheme based on blockchain.•Experimental results demonstrate that our solution is better than PBFT, G-PBFT and CPBFT. As an application of Internet of Things (IoT) technology, the Internet of Vehicles (IoV) faces two main security issues: (1) the central server of the IoV may not be powerful enough to support the centralized authentication of the rapidly increasing connected vehicles, (2) the IoV itself may not be robust enough to single-node attacks. To address these issues, in this paper, we propose SG-PBFT (Score Grouping-PBFT), a secure and efficient distributed consensus algorithm for blockchain applications in the IoV. The distributed structure can reduce the pressure on the central server and decrease the risk of single-node attacks. The SG-PBFT consensus algorithm improves the traditional practical Byzantine fault tolerance (PBFT) consensus algorithm by optimizing the PBFT consensus process and using a score grouping mechanism to achieve a higher consensus efficiency. The experimental results show that the method can greatly improve the consistency efficiency and effectively prevent single-node attacks. Specifically, when the number of consensus nodes reaches 1000, the consensus time of our algorithm is only about 27% of what is required for the state-of-the-art PBFT consensus algorithm. Our proposed SG-PBFT algorithm is versatile and can be used in other application scenarios which require high consensus efficiency.